2016
DOI: 10.1016/j.radcr.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Intralobar pulmonary sequestration in elderly woman: a rare case report with emphasis on imaging findings

Abstract: Intralobar pulmonary sequestration is a rare malformation that predisposes to recurrent respiratory infections. It is difficult to diagnose unless a more extensive directed investigation (to the vasculature and pulmonary parenchyma) is take on. Failure to diagnose and treat this condition can lead to recurrent pneumonia and fatal hemoptysis. Most cases are diagnosed before the age of 20 years. In this report, we present an extremely rare case of elderly woman with initial diagnosis of intralobar sequestration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…It has been reported that 60% of ILPS is diagnosed before the age of 20, and it is seldom found in patients aged 40 years or older [1]. Because of the nonspecific symptoms, it is often difficult to diagnose without direct investigation, and imaging of the vasculature and pulmonary parenchyma is done [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 60% of ILPS is diagnosed before the age of 20, and it is seldom found in patients aged 40 years or older [1]. Because of the nonspecific symptoms, it is often difficult to diagnose without direct investigation, and imaging of the vasculature and pulmonary parenchyma is done [4].…”
Section: Discussionmentioning
confidence: 99%
“…The sequestration subsequently receives systemic arterial supply instead of the normal pulmonary arterial supply . Intralobar pulmonary sequestrations receive anomalous systemic arterial supply predominantly deriving from the descending thoracic aorta (72%), abdominal aorta (21%), and, rarely, the intercostal arteries (3%) . The majority of intralobar sequestrations are drained by normal pulmonary veins into the left atrium .…”
Section: Discussionmentioning
confidence: 99%
“…Patients can present with an incidental pulmonary lesion on imaging while asymptomatic . However, patients may present with cough, fever, recurrent pneumonia, chest pain, and in a small number of cases, hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It should be noted that this type of malformation is diagnosed extremely rarely in individuals older than 60 years. 13,14 Montjoy et al reported three adult patients with pulmonary sequestration; they were aged 57 to 62 years, 8 and the oldest patient in the Gompelmann series from Germany was 59 years old. 7 In a large series from Florida including 29 patients with pulmonary sequestration published by Tashtoush et al, almost two thirds of individuals were adults, with the oldest being 70 years old.…”
Section: Discussionmentioning
confidence: 99%